2021
DOI: 10.5624/isd.20200095
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of panoramic radiography in predicting proximity of third molars to the mandibular canal: A comparison using cone-beam computed tomography

Abstract: Purpose The purpose of this study was to analyze the reliability of 7 panoramic radiographic signs for predicting proximity of the root apices of mandibular third molars to the mandibular canal using cone-beam computed tomography and to correlate these findings with the Pell and Gregory and the Winter classification systems. Materials and Methods An observational, cross-sectional, descriptive study was conducted on 74 patients with bilateral impacted mandibular third mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 21 publications
(7 reference statements)
4
13
0
3
Order By: Relevance
“…In mandibular M3s, superimposition of M3 onto the mandibular canal was considered as a risk factor of close contact, and several signs of superimposition such as darkening of the root or loss of the cortical line of the canal on panoramic images were also evaluated. 17 18 19 This study revealed superimposition to be a major risk factor, underscoring the need for further research on maxillary M3s. Although previous studies did not address superimposition, a few studies revealed that direct contact of M3 with the root surface of M2 is a major risk factor for ERR.…”
Section: Discussionmentioning
confidence: 70%
“…In mandibular M3s, superimposition of M3 onto the mandibular canal was considered as a risk factor of close contact, and several signs of superimposition such as darkening of the root or loss of the cortical line of the canal on panoramic images were also evaluated. 17 18 19 This study revealed superimposition to be a major risk factor, underscoring the need for further research on maxillary M3s. Although previous studies did not address superimposition, a few studies revealed that direct contact of M3 with the root surface of M2 is a major risk factor for ERR.…”
Section: Discussionmentioning
confidence: 70%
“…Most previous work using these classi cation systems in relation to a coronectomy has focused on root migration of mandibular third molars following a coronectomy. A few studies have used these classi cation systems to assess the diagnostic value of panoramic radiographs in predicting a true relationship between the mandibular third molar and the IAN [16, 17,19,20]. In those investigations, the impaction pattern was compared with a gold standard, either a CT or cone-beam CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Una imagen 3D permite observar tres planos anatómicos a diferencia de una imagen 2D que muestra únicamente dos planos de una estructura tridimensional. El profesional debe tener en cuenta que la presencia de oscurecimiento, desviación o estrechamiento de la raíz junto con la interrupción del CDI en una RP determina una nueva toma radiográfica, para la cual el método de elección será un estudio CBCT (Nunes et al, 2021).…”
Section: Discussionunclassified
“…3.6 Fiabilidad de la radiografía panorámica para predecir la proximidad de los terceros molares al canal mandibular: una comparación mediante tomografía computarizada de haz cónico Otro estudio realizado por Nunes y Cols., en el 2021 analiza la confiabilidad de los estudios radiográficos (RP y CBCT), en el cual se buscó observar la posición de los ápices dentales y su relación con el CDI. Sin embargo, las RP presentan una distorsión referente a las medidas lineales y superposición de estructuras; por lo cual el método radiográfico de mayor precisión es una CBCT debido a los múltiples planos que presenta, además este estudio clasificó de 3 maneras la posición de los 3MM con sus estructuras adyacentes según (Nunes et al, 2021):…”
Section: ¿Indica El Sistema De Clasificación De Winter O Pell Y Gregory La Posición Apical De Los Terceros Molares Mandibulares Impactadounclassified
See 1 more Smart Citation